Is the Indonesian Millennial Workforce Attracted to Companies with Green HRM Strategies? - Annah Dhiatul Ilmia; Maria Jacinta Arquisola (Jurnal Internasional Penelitian Bisnis Terapan, 2022)
Nowadays, the millennial workforce dominates Indonesia’s demographic bonus. This generation is more aware of environmental issues, and this drives industries to apply green human resource management (GHRM). This study aims to measure the influence of GHRM strategies in attracting the millennial workforce. Using non-probability sampling, a total of 340 millennials between 19–39 years old, employed or looking for a job, participated in this study. Using multiple regression analysis, the study found that the millennial workforce is attracted to industries where GHRM strategies are applied to measure work performance while industries that conduct less-innovative green training are the least attractive. It implies that companies that concern with environmental sustainability goals and action, as well as having more innovative green training programs, are more appealing to the millennials. This is the first study of its kind that observes the viability of green HRM practices in recruitment, suggesting that industries will become more attractive to the millennial workforce if organizational resources and attention are focused on green areas of human resource management. Therefore, industries are advised to implement GHRM sooner to attract more millennials and help companies achieve sustainability goals.